Long-Term Effects of Labor Migration in the Philippines: "Napakasakit, Kuya Eddie!" - Jose Ramon G. Albert; Ma. Teresa Habitan; Aubrey D. Tabuga; Jana Flor V. Vizmanos; Mika S. Mu\~noz; Angelo C. Hernandez (Philippine Institute for Development Studies (PIDS), 2023)
As the country witnesses a steady export of its human resources, it becomes imperative to explore not only the immediate impacts of labor migration on the Philippine economy, but also its long-term consequences on both OFWs and the families they leave behind. This study examines the various effects of labor migration on OFWs and their families, including the economic benefits and social costs (e.g., family dynamics, child outcomes in terms of labor, health and education) of the diaspora, and what has government done to assist these modernday heroes. Remittances sent home by OFWs have become a major contributor to the Philippine economy, representing around 10% of GDP. This provides income for families and supports consumer spending. However, labor migration has led to divided families and complex transnational relationships between OFWs and their families in the Philippines. While remittances support loved ones, being miles away from loved ones can cause psychic pains. Findings from interviews with OFWs and their families also suggest that young OFWs dream of retiring early but may not be provided systematic support for financial literacy. The paper calls for strengthening reinforcement of legal frameworks, enhancing the labor market, improving social protection programs for OFWs and their families. equipping them with necessary skills to achieve financial sustainability, and regularly monitoring OFW conditions for evidence-informed policymaking.
Keywords: 330; labor migration; overseas Filipino workers; OFW; labor export; diaspora